(3GdeYGfjs - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s
(3ChdgG (B:s
(3GdHGH GdKGfj ef cJGH GdeYGfj aj GdEaJNGQ GHf fHGJg(B: (3dHSJ ef GdMhGOK cd KhmH Shi KhH GdePdI hGdghGf s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO efg(B: (3bO bdJ deG bGd dj bGFd bO UGQ ofYeGf Edi QeSg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3ajg VHWs
(3bWYI efgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B240s
Keywords: (3GdCOHs